Household portfolios in Türkiye: Results from the household finance and consumption survey - Evren Ceritoǧlu; Seyit Mümin Cilasun; Müşerref Küçükbayrak; Özlem Sevinç (Central Bank Review (CBR), 2023)
This paper analyzes the distribution of household portfolios in Türkiye using a fresh data set, the Central Bank of the Republic of Türkiye - Household Finance and Consumption Survey. The empirical analysis concentrates on the motives behind household saving preferences and the distribution of household portfolios. Moreover, the financial situation of households in Türkiye is compared with Euro area countries. First, we find that income and household characteristics are among the leading determinants of households' portfolio choices in Türkiye. Second, we reveal that households' portfolios are under-diversified, since they own relatively small amounts of financial wealth and hold a few types of financial assets. Furthermore, risky asset categories such as shares of publicly traded companies are rarely included among them. Third, households are more likely to invest in financial assets as their income increases, but the share of financial assets in total wealth remains subdued as household income increases, since at that point real estate wealth becomes dominant. Finally, we discover that households are more likely to be in debt in Türkiye compared to households from the Euro area. Additionally, they are more likely to accumulate non-collateralized debt and also private debt, which is owed to friends and relatives to be repaid. However, the percentage of households with mortgage debt and the share of mortgage debt in total household liabilities are smaller in Türkiye, suggesting that many households have to rely on their own funds or private loans to purchase homes. As a result, we can argue that households need to be encouraged to invest a larger share of their wealth in financial assets to raise household savings and to deepen financial markets in Türkiye.
Keywords: C21; D12; D14; D31; 330; Household finance; Housing wealth; Financial assets; Income and wealth distribution